Chemical Changes in Dairy Products Resulting from Cholesterol Removal Using Beta Cyclodextrins - Priyanka, Malik; Christophe, Blecker (Current Nutrition & Food Science, 2017)
Background: Milk and milk products are a major source of dietary cholesterol. Beta Cyclodextrin (βCD) has emerged as one of the most preferred cholesterol removal aids. The literature demonstrates a number of studies that explains the methodology for cholesterol removal from dairy products. In this review, the characteristics of β CD and practical aspects of utilizing this compound as a processing aid to remove cholesterol from dairy products are discussed. Methods: Online research content related to cholesterol removal from milk and milk products was collected by undertaking a structured search of the bibliographic database. The available data online for the magnitude of compositional changes has been presented in a tabular form in this review article, which would facilitate the reader to have an overview. Further, the possible reasons for these changes and the consequences have been discussed. Results: The structural characteristics of βCD and processing conditions involved in cholesterol removal indicates possible loss of non-cholesterol molecules. Removal of cholesterol and non-cholesterol molecules results in altering the chemical composition and other physico-chemical properties of dairy products. These changes also have an effect on the sensory, rheological and storage properties of dairy products. In addition, this review also presents the global regulatory status and usage of βCD. Conclusion: From technological point of view, removal of cholesterol and non-cholesterol molecules also alters characteristics of dairy products such as storage stability and sensorial acceptability. However, the magnitude of these changes can be minimized by optimizing conditions of cholesterol removal.
Keywords: physico-chemical properties